2006
DOI: 10.1016/j.physletb.2005.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transfer followed by breakup in 7Li+65Cu

Abstract: The observation of a large cross-section for the α + d channel compared to breakup into the α + t channel from an exclusive measurement for the 7 Li+ 65 Cu system at 25 MeV is presented. A detailed analysis of the angular distribution using coupled channels Born approximation calculations has provided clear evidence that the observed α + d events arise from a two step process, i.e. direct transfer to the 2.186 MeV (3 + ) resonance in the α + d continuum of 6 Li followed by breakup, and are not due to final sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
95
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 39 publications
13
95
1
1
Order By: Relevance
“…4b are from the 201,202 Hg residues, of the composite system 204 Hg formed after capture of 6 He. The γ-ray transitions from 199,200 Pt, corresponding to one and two neutron transfer reactions are observed in the α, d and p gated spectra resulting from neutron transfer followed by breakup reactions [13]. The peaks at 366 keV and 241 keV in Fig.…”
Section: Plotted Inmentioning
confidence: 92%
“…4b are from the 201,202 Hg residues, of the composite system 204 Hg formed after capture of 6 He. The γ-ray transitions from 199,200 Pt, corresponding to one and two neutron transfer reactions are observed in the α, d and p gated spectra resulting from neutron transfer followed by breakup reactions [13]. The peaks at 366 keV and 241 keV in Fig.…”
Section: Plotted Inmentioning
confidence: 92%
“…3 (a). The data lie mainly in two distinct bands -one shows small θ 12 for all values of β with a tight correlation; the other has much larger θ 12 with a larger spread for a given β. That such bands emerge from the fairly featureless (except for the peak at 92 keV) E rel spectrum shown in Fig.…”
Section: (A)mentioning
confidence: 97%
“…However, many works (e.g. [11][12][13][14]) have indicated that the picture is not so simple, as transfer-triggered breakup, which can be important, is neglected. In 6 Li, 7 Li and 9 Be induced reactions for example, these channels are highly probable.…”
mentioning
confidence: 99%
“…The second breakup mode was sequential (resonant) breakup [10,11] which proceeds sequentially by first exciting the nuclei, via Coulomb excitation, to it continuum state which then dissociates into its cluster fragments. Further observations showed breakup triggered by nucleon transfer [12][13][14] also played an important role. More recent observations of suppression of complete fusion (∼ 30%) in reactions of Li was generally associated with their low breakup threshold energies [15][16][17].…”
Section: Introductionmentioning
confidence: 95%